PKM Second Shop Di Kota Payakumbuh Provinsi Sumatera Barat - Rosa, Yenni Del; Abdilla, Mohammad; Yendra, Nofri; Riski, Tri Rachmat; Hastini, Lasti Yossi; Putri, Siska Lusia; Saputra, Albi; A, Saadi Maimun (LPPM Universitas Dharma Andalas, 2025)
The second-hand import shoes business is currently growing quite rapidly so that people do not need to buy it at a high price. Genesis second shop sells various brands offline and online. The turnover of Genesis second shop per month is around IDR 10 million - IDR 12 million per month, the shop rent is IDR 11 million per year and is assisted by 1 employee. The priority problem of the Genesis second shop business is about market share and marketing strategy. The method of implementing counseling activities using lectures, discussions and practices. The purpose of the activity is for partners to know about market share and marketing strategies. The market share of Genesis second shop is all levels of lower and upper economic society of various ages. The Genesis second shop marketing strategy is carried out by paying attention to the 4P elements and improving existing marketing strategies and alternative marketing channels.